2012
DOI: 10.1242/dev.067058
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic retinoic acid signaling affects outflow tract cushion development through suppression of the myocardial Tbx2-Tgfβ2 pathway

Abstract: SUMMARYThe progress of molecular genetics has enabled us to identify the genes responsible for congenital heart malformations. However, recent studies suggest that congenital heart diseases are induced not only by mutations in certain genes, but also by abnormal maternal factors. A high concentration of maternal retinoic acid (RA), the active derivative of vitamin A, is well known as a teratogenic agent that can cause developmental defects. Our previous studies have shown that the maternal administration of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…We speculate that the elevated TGFβ2 observed in Fbln1 nulls causes an increase in Snail1 expression and a subsequent increase in EMT in the proximal OFT. This would be consistent with previous studies showing that TGFβ2 directly induces transcription of Snail1, which is implicated in the initiation of EMT (Niessen et al, 2008; Timmerman et al, 2004), and that increased TGFβ2 expression causes increased EMT (Shirai et al, 2009) and a hypercellular cushion phenotype (Sakabe et al, 2012; Shirai et al, 2009). Furthermore, the induction of Snail1 expression by TGFβ2 treatment has been shown to rescue EMT defects in the developing heart (Niessen et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We speculate that the elevated TGFβ2 observed in Fbln1 nulls causes an increase in Snail1 expression and a subsequent increase in EMT in the proximal OFT. This would be consistent with previous studies showing that TGFβ2 directly induces transcription of Snail1, which is implicated in the initiation of EMT (Niessen et al, 2008; Timmerman et al, 2004), and that increased TGFβ2 expression causes increased EMT (Shirai et al, 2009) and a hypercellular cushion phenotype (Sakabe et al, 2012; Shirai et al, 2009). Furthermore, the induction of Snail1 expression by TGFβ2 treatment has been shown to rescue EMT defects in the developing heart (Niessen et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Further analysis showed that hyaluronan (produced by Has-2) was required for ErbB receptor activation in order to induce EMT (Camenisch et al, 2002). Although soluble growth factors (Bai et al, 2013; Dor et al, 2001; Garside et al, 2012; Sakabe et al, 2012) involved in OFT endocardial cushion EMT have been extensively studied, our understanding of how ECM proteins present in the proximal cushion potentiate these signals is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In explant culture, endocardial cells of Tmem100 null embryos did not show EndMT in response to the treatment with TGFb2 and BMP2, well-established EndMT stimulants secreted from myocardial cells (Nakajima et al, 1997;Sakabe et al, 2012). Since TGFb/BMP-activated Smad signaling in endocardial cells appeared unaltered in Tmem100 null embryos, a signaling pathway functioning in concert with Smad signaling is likely to be defective in endocardial cells.…”
Section: Developmental Dynamicsmentioning
confidence: 94%
“…Alterations in RA signaling in several animal model systems recapitulate phenotypes associated with human congenital heart defects including DiGeorge Syndrome, 20, 21 transposition of the great arteries, 22 ventricular septal defects, persistent truncus arteriosus, double outlet right ventricle, 23 hypoplastic ventricular chambers 24 and tetralogy of fallot. 25 Defects of the outflow tract are largely attributed to the established roles that RA signaling plays in cardiac neural crest and second heart field cell lineages.…”
Section: Introductionmentioning
confidence: 96%